2016
DOI: 10.3109/1547691x.2015.1132288
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of EBV transformation of human memory B-cells isolated by FACS and MACS techniques

Abstract: Several studies have been performed to develop effective neutralizing monoclonal antibodies. The Epstein-Barr virus (EBV) can efficiently immortalize B-cells to establish lymphoblastoid cell lines (LCL) and so it has been used extensively for transformation of B-cells to produce and secrete immunoglobulin. The present study addressed the effect of TLR7/8 agonist (R848), feeder cells layer and fluorescence-activated cell sorting (FACS) and magnetic-activated cell sorting (MACS) cell separation methods on the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Few rigorous attempts to characterize and measure the effects of cell sorting on a range of sample types using modern technologies have been undertaken. [2][3][4][5][6][7] However, an understanding of the effects of cell sorting on samples of various kinds can guide researchers to predict whether sorting could influence a critical result and inform how to plan for addition controls or validation. In this study, cell cycle analysis and gene expression results from 3 sorting experiments using different cell types that encompassed different sites, instrument models, nozzle diameters, pressures, and exposure to UV laser illumination were performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few rigorous attempts to characterize and measure the effects of cell sorting on a range of sample types using modern technologies have been undertaken. [2][3][4][5][6][7] However, an understanding of the effects of cell sorting on samples of various kinds can guide researchers to predict whether sorting could influence a critical result and inform how to plan for addition controls or validation. In this study, cell cycle analysis and gene expression results from 3 sorting experiments using different cell types that encompassed different sites, instrument models, nozzle diameters, pressures, and exposure to UV laser illumination were performed.…”
Section: Discussionmentioning
confidence: 99%
“…2 In another study, Richardson et al 3 observed minimal gene expression changes in different populations of mouse mammary cell subsets when examined immediately after cell sorting. Sadreddini et al 4 demonstrated that magnetically activated cell sorting resulted in a higher transformation efficiency of memory B cells by Epstein-Barr virus when compared with traditional cell sorting. A study that examined the effect of sorting on human peripheral blood CD8 + cells observed sorting-induced activation of MAPK p38 with minimal functional changes.…”
Section: Introductionmentioning
confidence: 99%
“…The sorted cells can be used in a variety of applications including disease modeling, drug testing and characterization (i.e., lineage and gene expression) samples. For example, Sadreddini et al 45 investigated the effect of cell sorting on the transformation efficiency of antibody producing memory B-cells. The B-cells had been transformed with Epstein-Barr virus which caused them to transform into immortal lymphoblastoid cells and proliferate indefinitely.…”
Section: Isolation Of Naturally Occurring Cell Subpopulationsmentioning
confidence: 99%
“…Thus, the exposure of cells within the sorter to factors that may alter their native state has the potential to affect the function of the sorted cell population(s) (ie, cytokine production, proliferation) and ultimately affect experimental results, especially when sorting to single cells. [1], [2], [3], [4], [5], [6], [7], [8] In any laboratory, experiments must be performed in controlled, clean environments to minimize the alteration of results because of external factors. Common laboratory biological contaminants include bacteria, molds, yeasts, and mycoplasma.…”
Section: Introductionmentioning
confidence: 99%